Neural network PC tools a practical guide - Eberhart, Russell C.; Dobbins, Roy W. (Academic Press, 1990)
This is the first practical guide that enables you to actually work with artificial neural networks on your personal computer. It provides basic information on neural networks, as well as the following special features:
Includes bibliographical references (pages 321-327) and index
Keywords: Ordinateurs neuronaux; Circuit neuronique; Micro-ordinateurs; Microcomputers; Neural computers; Neural networks (Neurobiology); Personal Computer; Neurocomputer; Neuronales Netz; Mikrocomputer; Aufsatzsammlung